Pemanfaatan Daun Kelor Sebagai Minuman Herbal Dalam Rangka Mencegah Penyebaran Covid-19 - Marten Umbu Nganji; Lusia Danga Lewu; Uska Peku Jawang; Yonce Melyanus Killa; Sri Ita Tarigan (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: Moringa leaves can be processed in various food and beverage products such as clear vegetables, juice, omelette, chips, nastar, donuts, bakwan and Moringa leaf noodles. In addition, Moringa leaves can be processed as herbal drinks. Currently, with the covid-19 pandemic conditions around the world, many alternative herbal ingredients are consumed by the public to increase body nutrition in order to prevent transmission of the virus, one of which is Moringa leaves. Moringa plants are high in nutrients, such as vitamin C, calcium, vitamin A, potassium, and protein. The purpose of implementing this PkM activity is to provide information and, to provide assistance to the community in utilizing Moringa plants to prevent Covid-19, as well as to improve community skills in making Moringa herbal drink to prevent Covid-19. This PkM was held at the Ori Angu Farmers Group in Pambotanjara Village, with a series of activities including the socialization of the importance of Moringa leaves, the preparation of raw materials for making herbal moringa drinks, and the practice of manufacturing Moringa leaf herbal drink products. The results of this activity were the socialization of the use of Moringa leaves as a way to increase immunity in order to prevent viruses and the practice of making Moringa leaf tea with members of farmer groups, students and lecturers at the Ori Angu Farmer Group, Pambotanjara Village.Keywords: herbal drink; moringa leaves; prevents covid-19Abstrak: Daun kelor dapat diolah dalam berbagai produk makanan dan minuman seperti sayur bening, juice, omelet, keripik, nastar, donat, bakwan dan mie daun kelor. Selain itu, daun kelor dapat diolah sebagai minuman herbal. Saat ini, dengan adanya kondisi pandemik covid-19 di seluruh dunia, banyak alternatif bahan herbal yang dikonsumsi oleh masyarakat untuk menambah nutrisi tubuh agar dapat mencegah terjadinya penularan virus tersebut, salah satunya adalah daun kelor. Tanaman kelor memiliki nutrisi tinggi, seperti vitamin C, kandungan kalsium, vitamin A, kandungan potasium, dan protein. Tujuan pelaksanaan kegiatan PkM ini adalah untuk memberikan informasi dan, melakukan pendampingan kepada masyarakat dalam memanfaatkan tanaman kelor untuk mencegah covid-19, serta meningkatkan keterampilan masyarakat dalam pembuatan minuman herbal daun kelor dalam mencegah covid-19. PkM ini dilaksanakan di Kelompok Tani Ori Angu Desa Pambotanjara dengan runtutan kegiatan adalah sosialisasi pentingnya daun kelor, persiapan bahan baku pembuatan minuman herbal daun kelor, dan praktik pembuatan produk minuman herbal daun kelor. Hasil dari kegiatan ini adalah terlaksananya sosialisasi pemanfaatan daun kelor sebagai salah satu cara menambah imunitas tubuh dalam rangka mencegah virus dan dilaksanakannya praktik pembuatan teh daun kelor bersama anggota kelompok tani, mahasiswa dan dosen di Kelompok Tani Ori Angu Desa Pambotanjara.Kata kunci: daun kelor; mencegah covid-19; minuman herbal